TIPE1‐mediated autophagy suppression promotes nasopharyngeal carcinoma cell proliferation via the AMPK/mTOR signalling pathway. Issue 16 (25th June 2020) - Liu, Yongliang; Qi, Xiangqin; Zhao, Zhenan; Song, Daoliang; Wang, Lianqing; Zhai, Qiaoli; Zhang, Xiaoning; Zhao, Peiqing; Xiang, Xinxin
Abstract: Recent studies have shown that tumour necrosis factor‐α–induced protein 8 like‐1(TIPE1) plays distinct roles in different cancers. TIPE1 inhibits tumour proliferation and metastasis in a variety of tumours but acts as an oncogene in cervical cancer. The role of TIPE1 in nasopharyngeal carcinoma (NPC) remains unknown. Interestingly, TIPE1 expression was remarkably increased in NPC tissue samples compared to adjacent normal nasopharyngeal epithelial tissue samples in our study. TIPE1 expression was positively correlated with that of the proliferation marker Ki67 and negatively correlated with patient lifespan. In vitro, TIPE1 inhibited autophagy and induced cell proliferation in TIPE1‐overexpressing CNE‐1 and CNE‐2Z cells. In addition, knocking down TIPE1 expression promoted autophagy and decreased proliferation, whereas overexpressing TIPE1 increased the levels of pmTOR, pS6 and P62 and decreased the level of pAMPK and the LC3B. Furthermore, the decrease in autophagy was remarkably rescued in TIPE1‐overexpressing CNE‐1 and CNE‐2Z cells treated with the AMPK activator AICAR. In addition, TIPE1 promoted tumour growth in BALB/c nude mice. Taken together, results indicate that TIPE1 promotes NPC progression by inhibiting autophagy and inducing cell proliferation via the AMPK/mTOR signalling pathway. Thus, TIPE1 could potentially be used as a valuable diagnostic and prognostic biomarker for NPC.